Analgesic efficacy of bupivacaine alone versus bupivacaine plus dexmedetomidine in penile block for hypospadias surgery - Kamali, Farnaz; Mahdavi, Alireza; Razavi, Seyed Javad; Sadeghi, Afsaneh; Sarafi, Mehdi (Iranian Journal of Pediatric Surgery, 2019)
Introduction: Hypospadias is a common pediatric surgical procedure. Early postoperative pain management is essential to inhibit pain impulses and endocrine responses; leading to decreased mortality and morbidity and lower rate of agitation and faster return to normal functional status. This study evaluates the analgesic efficacy of bupivacaine alone versus bupivacaine plus dexmedetomidine in penile block for hypospadias surgery. Materials and Methods: In this randomized clinical trial, 64 children undergoing hypospadias surgery in a referral center in Tehran, Iran during 2018 were enrolled and randomly assigned to receive either bupivacaine 0.25% alone 0.2 ml/kg or bupivacaine 0.25% 0.2 ml/kg plus dexmedetomidine 0.3 μg/kg. After performing penile block, reversion of anesthesia was carried out and patients were extubated after regaining complete consciousness. Patients were monitored for 24 hours for pain according to FLACC scale and also the analgesia and block duration was determined. Results: Mean analgesia duration was 2.63±0.9 and 2.03±0.5 hours in the combination group and alone group respectively which was significant (P=0.003). The mean duration of block was significantly longer in the combination group (P=0.001). Conclusions: According to the results it may be concluded that addition of dexmedetomidine to bupivacaine in hypospadias surgeries would result in longer analgesia and block duration; without addition of adverse effects.